JPGN reports - North American Society for Pediatric Gastroenterology, Hepatology and Nutrition; European Society for Pediatric Gastroenterology, Hepatology and Nutrition (Wolters Kluwer Health, 2020)
"JPGN REPORTS provides a forum for exchange of information pertinent to the fields of gastroenterology, hepatology, and nutrition aimed to enhance the care of pediatric and young adult patients and for investigators to pursue related areas requiring further study."
Keywords: Pediatric gastroenterology : Periodicals; Children : Nutrition : Periodicals; Infant Nutritional Physiological Phenomena; Child Nutritional Physiological Phenomena; Gastrointestinal Diseases; Infant; Child; Children : Nutrition; Pediatric gastroenterology